Pengaruh Penambahan Kopi Arabica Coffea Arabica Terhadap Pembuatan Selai Terong Belanda Solanum Betaceum - Gideon Tonapa Rinding; Fatmawati Fatmawati; Abdul Halik (PALLANGGA: Journal of Agriculture Science and Research, 2023)
Dutch eggplant is a fruit that has good nutrition for health, but processing of Dutch eggplant as a food product is still minimal. Arabica coffee is a commodity that is widely available in Indonesia and has a high selling price. Dutch eggplant processing into jam is a practical form of food diversification. This study aims to determine the best addition concentration between Dutch eggplant and arabica coffee extract for total dissolved solids, degree of acidity (pH), and organoleptic tests. The research treatments were Dutch eggplant with a concentration of 500 grams and arabica coffee extract with a concentration of 5%, 10%, 15%, and 20%. Data analysis used a completely randomized design (CRD) with four treatment levels and three replications. Observational data were analysed using analysis of variance (ANOVA) and BNT follow-up test. Based on the results of the study, the addition of Dutch eggplant with Arabica coffee extract was significantly different in terms of total dissolved solids, degree of acidity (pH), aroma, texture, taste, and spread ability. The best result from Dutch eggplant jam with the addition of arabica coffee extract was the addition of 10% coffee extract in terms of total dissolved solids 68.49, degree of acidity (pH) 5.92, aroma 3.59 (likes), texture 4.13 (likes), taste 4.15 (like), and spread ability 4.19 (like). Terong belanda merupakan buah yang memiliki gizi yang baik untuk kesehatan, namun pengolahan terong belanda sebagai produk pangan masih sangat minim dilakukan. Kopi arabica merupakan salah satu komoditi yang banyak didapatkan di Indonesia dan memiliki harga jual yang tinggi. Pengolahan terong belanda menjadi selai merupakan salah satu bentuk diversifikasi pangan yang praktis. Penelitian ini bertujuan untuk mengetahui konsentrasi penambahan terbaik antara terong belanda dengan ekstrak kopi arabica terhadap total padatan terlarut, derajat keasaman (pH), dan uji organoleptik. Perlakuan penelitian yaitu terong belanda dengan konsentrasi 500 g dan ekstrak kopi arabica dengan konsentrasi 5%, 10%, 15%, dan 20%. Analisis data menggunakan metode Rancangan Acak Lengkap (RAL) dengan empat taraf perlakuan dan tiga kali ulangan. Data hasil pengamatan dianalisis menggunakan analisis keragaman (ANOVA) dan uji lanjutan BNT. Berdasarkan hasil penelitian bahwa penambahan terong belanda dengan ekstrak kopi arabica berbeda nyata terhadap total padatan terlarut, derajat keasaman (pH), aroma, tekstur, citarasa, dan daya oles. Hasil terbaik dari selai terong belanda dengan penambahan ekstrak kopi arabica adalah penambahan ekstrak kopi 10% ditinjau dari total padatan terlarut 68,49, derajat keasaman (pH) 5,92, aroma 3,59 (suka), tekstur 4,13 (suka), citarasa 4,15 (suka), dan daya oles 4,19 (suka).